Growth Cones: Structural, Molecular and Functional Relevance to Neuronal Migration, Regeneration and Reproductive Function - Mona Sharma; Anmol Garg; Tanya Gupta (Journal of Medical Academics)
The specialized cells of the human brain form a complex network responsible for neural processing and transmission via various electrochemical signaling pathways. A critical phenomenon in this signaling cascade is the formation of synaptic contacts between adjacent or distant neurons. During axonal growth and synaptogenesis, the developing axons exhibit a highly dynamic region at their leading edges, aptly described as the “growth cone.” These structures serve as the guiding force for extending axons by transducing attractive and repulsive cues into cellular signals that modulate the internal cytoskeletal environment, thereby directing axonal growth toward or away from stimuli within the surrounding neural circuitry. The process of axonal migration is essential during embryonic and adult neurogenesis, neuronal connectivity, and neural regeneration. Consequently, understanding the structural and molecular regulation of growth cone formation is crucial for elucidating the intricately orchestrated events underlying neuronal migration and connectivity. This knowledge is also vital because the functional competency of the adult nervous system is influenced by the connections established during axonal growth and migration. This review aims to provide a comprehensive overview of the structural and functional aspects of growth cones, along with the molecular mechanisms underlying their formation, to shed light on the critical processes governing neuronal migration and connectivity. The clinical relevance of growth cones will be highlighted in neural regeneration, neural variations, and gonadotropin-releasing hormone (GnRH) migration initiating reproductive system development.